2011
DOI: 10.1037/a0023190
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model of weekday stress and weekend recovery of students.

Abstract: In previous research on psychological stress recovery, recovery activities and recovery experiences have been studied separately rather than jointly. The present study advances previous knowledge about stress recovery by integrating the effects of these separate recovery constructs within a single study and examining them outside the work context. We propose and test an integrated model of the stress-recovery process that includes weekday stressors and weekend recovery activity behaviors, psychological recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
100
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(111 citation statements)
references
References 66 publications
10
100
1
Order By: Relevance
“…Since full-timers have more free time, a hobby serves as an effective coping strategy for recovery from academics and helps to maintain health. This finding concurs with other research (see Paul et al, 2007;Ragsdale et al, 2011;Sonnentag et al, 2008). Comparatively, more mature part-time students may cut out their recovery activities (Ragsdale et al, 2011;Sonnentag et al, 2008) as they prioritize their commitments.…”
Section: Stress Coping Mechanismssupporting
confidence: 91%
See 2 more Smart Citations
“…Since full-timers have more free time, a hobby serves as an effective coping strategy for recovery from academics and helps to maintain health. This finding concurs with other research (see Paul et al, 2007;Ragsdale et al, 2011;Sonnentag et al, 2008). Comparatively, more mature part-time students may cut out their recovery activities (Ragsdale et al, 2011;Sonnentag et al, 2008) as they prioritize their commitments.…”
Section: Stress Coping Mechanismssupporting
confidence: 91%
“…Eating more or emotional eating is another common stress reliever and supports Adam and Epel (2007) who studied the positive physiological responses that eating elicits. Similarly, we found that engaging in a hobby is also a stress reliever for our sample to sufficiently recover from the negative effects of the stressor (Ragsdale et al, 2011;Sonnentag et al, 2008). Arguably, a resultant calmer state of mind should allow for a more balanced decision-making-process about the stressor, that is, based more on fact-rather than heightened emotions.…”
Section: Stress Coping Mechanismssupporting
confidence: 50%
See 1 more Smart Citation
“…For example, Ragsdale et al, (2011) have already developed an integrative model of recovery among undergraduate students. They include in their model not only recovery experiences, but also recovery quality, need for recovery, and recovery activities (resource-providing and resourceconsuming activities).…”
Section: Introductionmentioning
confidence: 99%
“…They favoured a reduced version containing 12 items with the same four-dimensional factorial structure and satisfactory reliability coefficients, as will be outlined in the description of research instruments. Despite the importance that detachment is gaining in the workplace, currently, some authors have addressed the study of detachment among university students (Larson, 2006;Misra & Castillo, 2004;Ragsdale, Beehr, Grebner, & Han, 2011). It is important to highlight that students have greater difficulty in disconnecting from their work, due to the time they must dedicate to study outside the classroom.…”
Section: Introductionmentioning
confidence: 99%